2012
DOI: 10.3390/genes3040779
|View full text |Cite
|
Sign up to set email alerts
|

The Sound of Silence: RNAi in Poly (ADP-Ribose) Research

Abstract: Poly(ADP-ribosyl)-ation is a nonprotein posttranslational modification of proteins and plays an integral part in cell physiology and pathology. The metabolism of poly(ADP-ribose) (PAR) is regulated by its synthesis by poly(ADP-ribose) polymerases (PARPs) and on the catabolic side by poly(ADP-ribose) glycohydrolase (PARG). PARPs convert NAD+ molecules into PAR chains that interact covalently or noncovalently with target proteins and thereby modify their structure and functions. PAR synthesis is activated when P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…In agreement with this observation, proliferation analysis revealed that both PARP1 KO clones showed significantly slower proliferation rates compared to WT, while the overall cell cycle distribution appeared to be unaffected (Figure 2A and B). A plethora of reports from Parp1 KO mice and human cell culture studies using RNA interference and pharmacological inhibition of PARP activity showed that loss of PARP1 leads to a sensitization of cells towards genotoxic stimuli (31,32,52). To test if the same holds true in genetically-targeted HeLa PARP1 KO cells, we performed a clonogenic survival analysis of HeLa WT and PARP1 KO cells upon H 2 O 2 treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this observation, proliferation analysis revealed that both PARP1 KO clones showed significantly slower proliferation rates compared to WT, while the overall cell cycle distribution appeared to be unaffected (Figure 2A and B). A plethora of reports from Parp1 KO mice and human cell culture studies using RNA interference and pharmacological inhibition of PARP activity showed that loss of PARP1 leads to a sensitization of cells towards genotoxic stimuli (31,32,52). To test if the same holds true in genetically-targeted HeLa PARP1 KO cells, we performed a clonogenic survival analysis of HeLa WT and PARP1 KO cells upon H 2 O 2 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of our knowledge on PARP1 and PARylation has been obtained through a series of studies using three independently generated Parp1 knock-out mouse models and immortalized mouse embryonic fibroblasts (MEFs) derived thereof (2831), as well as siRNA-based knock-down approaches (32). Strikingly, a genetic double knock-out of Parp1 and Parp2 resulted in embryonic lethality in the mouse, thereby demonstrating a key function of PARylation during development (33).…”
Section: Introductionmentioning
confidence: 99%
“…However, the PARP1 homozygous null (-/-) mouse exhibits accelerated aging and spontaneous tumorigenesis [40], and human HCT116 colon carcinoma cells that are deficient in both PARP1 alleles by CRISPR/Cas9 knockout exhibited reduced growth rates, increased cellular senescence and DNA-damage, and aberrant interferon responses [33]. These findings highlight the importance of ablating PARP1 by other less drastic methods such as partial disruption of PARP1 protein synthesis by RNAi knockdown targeting PARP1 mRNA [41] and inhibition of PARP's PARylation activity with small molecule inhibitors [42]. To understand how PARP1 modulates influenza virus life cycle, we studied the relationship between PARP1, cellular PARylation, and activity of the IAV RdRP.…”
Section: Introductionmentioning
confidence: 99%